Performance of the Local and Standard Hazelnut Cultivars Grown in Samsun Province, Turkey - Beyhan, N; Demir, T (International Society Horticultural Science, 2001)
This study was carried out on hazelnut cultivars grown in Samsun province in Turkey during 1995 and 1996. Fruit characteristics of seven standard cultivars ('Tombul', 'Palaz', 'Sivri', 'Cakildak', 'Kalinkara', 'Yuvarlak Badem' and 'Acifindik') were compared to those of three local varieties ('Hanimfindigi', 'Yerlifindik' and 'Cevizfindigi'). 'Cevizfindigi' ranked highest for nut weight, kernel weight and nut and kernel size (4.01 g, 1.49 g, 23.44 mm and 16.79 mm, respectively). The values of the same parameters for 'Tombul' were 2.16 g, 1.14 g, 17.80 mm and 14.48 mm, respectively. The highest percent kernel (59.59%) and the lowest shell thickness (0.62 mm) were found in 'Hanimfindigi' while 'Tombul' was 52.78% and 1.06 mm, respectively. The blanching ratio of 'Tombul' was 96% compared to 99% in 'Palaz'. The highest double kernel frequency was 14% in 'Kalinkara'. Nut and kernel weight, percent kernel, nut and kernel size of some cultivars were lower in 1996 than in 1995.
5th International Congress on Hazelnut -- AUG 27-31, 2000 -- CORVALLIS, OR
Keywords: Corylus avellana; Filbert